A new soldier beetle Malthinellus exiguus sp. nov. (Coleoptera: Cantharidae) from the Ryukyus in southwestern Japan, with a key to Japanese species - Takahashi, Naoki (Zootaxa, 2018)
Malthinellus exiguus sp. nov., from the central Ryukyus in the southwestern part of Japan is described and illustrated. An identification key to the Japanese species and the checklist of the known species of Malthinellus are provided.